In-Silico Analysis of Genetic Mutations in BRAF and PMS2 for Biomarker Discovery to Transform Colorectal Cancer Research - Jahan, Nusrat; Arshad, Arslan; Samd Ullah; Nazir, Humera; Iftikhar Ud Din; Zafar, Muhammad Hammad; Shafiq, Shaista; Kanwal, Faheem; Azmat, Muhammad; Zafar, Imran (Indus Journal of Bioscience Research, 2025)
Point mutations in the PMS2 and BRAF genes have emerged as critical drivers of colorectal cancer, influencing key cellular processes such as mismatch repair and signal transduction. Understanding the impact of these mutations at the molecular level is essential for advancing cancer diagnostics and therapies. This study leverages advanced bioinformatics tools to systematically identify and evaluate potentially deleterious single nucleotide polymorphisms (SNPs) in the coding regions of PMS2 and BRAF. Using SIFT, PolyPhen-2, and I-Mutant 2.0, we assessed the functional impact of 2412 SNPs in PMS2 and 453 SNPs in BRAF. From these, 32 mutations in PMS2 and one in BRAF were predicted to be highly deleterious, with significant implications for protein stability and function. Specifically, PMS2 mutations such as c.137G>T (p.Ser46Ile) and c.383C>T (p.Ser128Leu) were found to disrupt the protein structure, potentially impairing its role in mismatch repair. The BRAF mutation V600E was identified as highly damaging, consistent with previous studies that associate it with oncogenic activation in several cancers. These results highlight the importance of computational approaches in predicting the pathogenicity of genetic mutations and their potential as therapeutic targets in colorectal cancer. This study establishes a foundation for future experimental and clinical research aimed at evaluating the therapeutic potential of targeting specific SNPs in colorectal cancer. Computational analysis identified 21 deleterious SNPs in PMS2 and one in BRAF, which may disrupt protein function. These findings underscore their potential significance in colorectal cancer progression and targeted therapeutic strategies.